Measuring Temperature and Humidity Using Arduino - Jawad, Hussien Essam Adnan; Rijah, Abdulhameed Dhari Hameed; Sanad, Abdalbacet Azez Ali; Alwan, Ahmed Adil Naim; Mankhi, Asaad Muzhr Mathbob (American Journal of Botany and Bioengineering, 2025)
Technology plays a crucial role in modern life, especially in home automation and healthcare applications. This study presents a system for measuring temperature and humidity using an Arduino-based setup, which is beneficial for both environmental monitoring and health management. The system utilizes a DHT11 sensor to collect real-time data, displayed on an LCD screen. The hardware includes an Arduino Uno board, jumper wires, LEDs, resistors, a buzzer, and a breadboard for easy assembly. The Arduino IDE ensures seamless integration of components. This device not only enhances indoor comfort and energy efficiency but also contributes to health safety by maintaining optimal environmental conditions, reducing risks of respiratory issues and heat stress. A buzzer provides alerts when temperature or humidity exceeds set thresholds, while LEDs indicate environmental status. This project demonstrates the practical use of embedded systems in climate control and healthcare, offering an affordable and efficient solution. Future enhancements may include wireless connectivity and data logging for improved usability.